Guinea : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2013)
This paper on Poverty Reduction Strategy Papers on Guinea explains medium-term development framework to achieve Millennium Development Goals and fulfill the authorities' vision of Guinea as an emerging economy in 15 to 25 years, respectful of human rights and gender equality and supportive of the rule of law. It sets out medium-term policies that Guinea should implement to place itself on a path to development that would allow it to fulfill its ambition to become an emerging economy by 2035. This scenario foresees strong and lasting average annual growth, supported by ambitious policies for modernization of agriculture.